2014
DOI: 10.1051/kmae/2014005
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput discrimination of bacteria isolated fromAstacus astacusandA. leptodactylus

Abstract: Key-words: crayfish, bacteria, MALDI-TOF MS, API 20EBacterial diseases and pathogens of crayfish are common, widespread, and occasionally causing serious mortalities. In order to take rapid measures for correct treatment of crayfish diseases, the turnover time and accuracy in bacterial identification is an issue. Bacteria isolated from tissues of apparently healthy Astacus astacus and A. leptodactylus were identified by the commercial phenotypic tests (API 20E) and by the matrix assisted laser induced desorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The need for comparison of MALDI-TOF MS data with results obtained from phenotypic and genotypic identification methods is still important for identification of environmental isolates. We confirmed that in our study where we isolated bacteria from tissues of apparently healthy freshwater crayfish (Topić Popović et al, 2014). From 25 relevant isolates, only one matched to the species when compared with conventional methods (Hafnia alvei), while API 20E and MALDI-TOF MS identified 60.86 % identically to the genus.…”
Section: Maldi-tof Ms Applicability For Environmental Isolates (Watersupporting
confidence: 86%
“…The need for comparison of MALDI-TOF MS data with results obtained from phenotypic and genotypic identification methods is still important for identification of environmental isolates. We confirmed that in our study where we isolated bacteria from tissues of apparently healthy freshwater crayfish (Topić Popović et al, 2014). From 25 relevant isolates, only one matched to the species when compared with conventional methods (Hafnia alvei), while API 20E and MALDI-TOF MS identified 60.86 % identically to the genus.…”
Section: Maldi-tof Ms Applicability For Environmental Isolates (Watersupporting
confidence: 86%
“…Concretely, the abundance in OW, UL, and OCU were 14.83, 19.41, and 23.22%, respectively. Generally, Pseudomonas was considered to be the dominant microbiota in crayfish [ 45 , 60 ]. However, because the total microbial load was unknown, although the relative abundance of Pseudomonas increased, it was not known whether this phenomenon was due to an increase in its absolute quantity or a decrease in the abundance of other microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, different species of Aeromonas isolates were unambiguously separated by hierarchical clustering by MALDI TOF MS which also gave a very rapid characterization of bacteria at the genus, species and strain level, thus proving its potential for speciating the unknown environmental bacterial isolates (Topic Popovic et al, 2014), although environmental Aeromonas isolates have a wider phenotypic diversity than isola Q3 tes obtained from clinical samples (Donohue et al, 2007). The genus Aeromonas comprises of over 20 species, and some of them are phenotypically very similar.…”
Section: Methodological Differences In Strain Discriminationmentioning
confidence: 99%